Efficacy of epidermal growth factor receptor-tyrosine kinase inhibitor for lung adenosquamous cell carcinoma harboring EGFR mutation: a retrospective study and pooled analysis - Xia, Xueming; Du, Wei; Zhang, Yan; Li, Yanying; Yu, Min; Liu, Yongmei (Frontiers in Oncology, 2024)
Objectives: To explore the efficacy of epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) on lung adenosquamous cell carcinoma (ASC) with EGFR mutation.Methods: Efficacy of EGFR-TKIs in the treatment of advanced or recurrent lung ASC with EGFR mutations was assessed retrospectively in 44 patients. Pooled analysis of 74 patients using EGFR-TKIs, including 30 patients selected from 11 publications, was conducted.In our retrospective research, patients treated with EGFR-TKI in ASC with EGFR mutations had objective response rate (ORR) of 54.5%, disease control rate (DCR) of 79.5%, median progression free survival (mPFS) of 8.8 months, and median overall survival (mOS) of 19.43 months, respectively. A pooled analysis reveals ORR, DCR, mPFS, and mOS are, respectively, 63.4%, 85.9%, 10.00 months, and 21.37 months for ASC patients. In patients with deletions in exon 19 and exon 21 L858R mutations, mPFS (11.0 versus 10.0 months, P=0.771) and mOS (23.67 versus 20.33 months, P=0.973) were similar. Erlotinib or gefitinib-treated patients had an overall survival trend that was superior to that of icotinib-treated patients.Conclusions: ASC harboring EGFR mutations can be treated with EGFR-TKI in a similar manner to Adenocarcinoma (ADC) harboring EGFR mutations. There is still a need for further investigation to identify the separate roles of ASC's two components in treating EGFR.